A case series study of omphalocele with associated anomalies: An embryogenic imperfection - Kasturi Kshitija; Krupa Elena; Seethamsetty Saritha; Sonta Savitha (Wolters Kluwer Medknow Publications, 2022)
Omphalocele is a developmental aberration which occurs during embryonic period in the fetal life. The fault in complete closure of the anterior abdominal wall leading to protrusion of the abdominal viscera mainly the small and large intestines with the liver into the base of umbilical cord insertion forms its main pathological feature. It differs from gastroschisis in that the eviscerated organs are covered by a thin amniotic peritoneal membrane, whereas in latter, the herniated contents are exposed exterior with no covering. In fetuses, this malformation is known to be complicated with abnormal karyotyping, other congenital abnormalities, and idiopathic syndromes which account for grave prognosis. Hence, the aim of our study was to analyze the clinical presentation and document seven cases of fetuses having omphalocele associated with anomalies and chromosomal aberrations leading to fetal dismissal.